2009
DOI: 10.1128/aem.00690-08
|View full text |Cite
|
Sign up to set email alerts
|

Coxiella burnetii Shedding Routes and Antibody Response after Outbreaks of Q Fever-Induced Abortion in Dairy Goat Herds

Abstract: Q fever is a zoonosis caused by Coxiella burnetii, a bacterium largely carried by ruminants and shed into milk, vaginal mucus, and feces. The main potential hazard to humans and animals is due to shedding of bacteria that can then persist in the environment and be aerosolized. The purpose of this study was to evaluate shedding after an outbreak of Q fever abortion in goat herds and to assess the relationship with the occurrence of abortions and antibody responses. Aborting and nonaborting goats were monitored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
129
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(136 citation statements)
references
References 29 publications
6
129
0
1
Order By: Relevance
“…Bacterial burdens in vaginal mucus and, to a lesser extent, in feces were also higher. These results are consistent with those previously obtained for sheep (17,20,21,35), goats (19,27,36), and cows (18). Low levels of C. burnetii DNA were also detected in milk (C T Ͼ30.5), which fits with the prevailing opinion among experts that sheep shed lower burdens of C. burnetii in milk than do cows and goats (3).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Bacterial burdens in vaginal mucus and, to a lesser extent, in feces were also higher. These results are consistent with those previously obtained for sheep (17,20,21,35), goats (19,27,36), and cows (18). Low levels of C. burnetii DNA were also detected in milk (C T Ͼ30.5), which fits with the prevailing opinion among experts that sheep shed lower burdens of C. burnetii in milk than do cows and goats (3).…”
Section: Discussionsupporting
confidence: 82%
“…Low levels of C. burnetii DNA were also detected in milk (C T Ͼ30.5), which fits with the prevailing opinion among experts that sheep shed lower burdens of C. burnetii in milk than do cows and goats (3). We also confirmed that vaginal and fecal shedding durations varied among ewes (17,20) and that shedding may be discontinuous, as in goats (19,23,25,26,37) and cows (18,24). The latter finding suggests that the number of C. burnetii shedders may be underestimated if only one shedding route is investigated and/or if the animals are not repeatedly tested over time.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…The diagnosis of C. burnetii by serological responses, which can be unspecific and unsensitive due to cross-reaction (Rousset et al, 2009) or subsensitive reactionsin samples from areas with a low or subclinical prevalence of Coxiellosis. In addition serological diagnostic methods are retrospective due to the timeframe for sero-conversion (3-4 weeks post infection), rendering them useless for timely treatment.…”
Section: Introductionmentioning
confidence: 99%